Induction of Emetic Response to Staphylococcal Enterotoxins in the House Musk Shrew (Suncus murinus) - Hu, Dong-Liang (American Society for Microbiology, 2003)
The emetic responses induced by staphylococcal enterotoxin A (SEA), SEB, SEC2, SED, SEE, SEG, SEH, and SEI in the house musk shrew (Suncus murinus) were investigated. SEA, SEE, and SEI showed higher emetic activity in the house musk shrew than the other SEs. SEB, SEC2, SED, SEG, and SEH also induced emetic responses in this animal model but relatively high doses were required. The house musk shrew appears to be a valuable model for studying the mechanisms of emetic reactions caused by SEs.